1989
DOI: 10.1111/j.1365-2133.1989.tb01372.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of circulating and in situ lymphocyte subsets and Langerhans cells in the skin and cervix of patients with chronic renal failure

Abstract: This study was designed to detect possible changes in the immunocytology of the human immune system in the skin, cervix and peripheral blood of patients with chronic renal failure (CRF) treated by conservative methods, haemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD). In the skin, Langerhans cell numbers were reduced in CRF, CAPD and HD patients but in the cervix, Langerhans cells were reduced only in the CRF patients. There was a preponderance of T suppressor lymphocytes compared with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
2
8
0
2
Order By: Relevance
“…We found that the cells involved in the humoral axis of immunity were consistent with those of reported studies [15, 24, 27, 28], providing evidence of a low proportion of B cells in HD patients. This could partly account for the altered antibody response in uremia.…”
Section: Discussionsupporting
confidence: 81%
“…We found that the cells involved in the humoral axis of immunity were consistent with those of reported studies [15, 24, 27, 28], providing evidence of a low proportion of B cells in HD patients. This could partly account for the altered antibody response in uremia.…”
Section: Discussionsupporting
confidence: 81%
“…19,20 We found that onychomycosis was the second most frequent (19.2%) nail disorder in our hemodialysis patient group. In two previous reports on these patients, the rates of onychomycosis were 6.2% 3 and 52%.…”
Section: Discussionmentioning
confidence: 96%
“…Direct evidence for this hypothesis is lacking, and only in mice it has been shown that GM-CSF administration increases the number of splenic dendritic cells, especially DC1 [27,28]. In hemodialysis patients a relative paucity of dendritic cells in the skin has been observed [29,30].…”
Section: Discussionmentioning
confidence: 96%